Evaluation of Current Perioperative Antimicrobial Regimens for the Prevention of Surgical Site Infections in Breast Implant-based Reconstructive Surgeries. Issue 7 (July 2019) - Viola, George M.; Rolston, Kenneth V.; Butler, Charles; Selber, Jesse; Reece, Gregory; Clemens, Mark; Villa, Mark; Raad, Issam I.; Baumann, Donald
Abstract : Background: Several steps to reduce the rate of postoperative surgical site infections (SSIs) have been implemented. The use of prophylactic antimicrobials targeting patient's microbial flora has been associated with a decrease in postoperative infections. We evaluated the relationship between perioperative antimicrobials, baseline microbial flora, and occurrence of SSIs. Methods: We prospectively enrolled 241 patients scheduled to receive a postmastectomy implant-based reconstructive procedure between September 2015 and January 2018. Axillary swab cultures were obtained preoperatively, and all recovered bacteria were identified. Surgeons were blinded to these results. The use of prophylactic perioperative antimicrobials was defined as concordant if the baseline axillary flora were susceptible to the given antibiotic and discordant if not. As Staphylococcus species are the most common pathogen causative for breast implant-related infections, patients colonized with these organisms were analyzed in detail. All patients were followed up for at least 6 months postoperatively and evaluated for SSIs. Results: A total of 238 patients (99%) received both perioperative and postoperative oral antimicrobials. The most common preoperative staphylococci axillary flora recovered were methicillin-sensitive coagulase-negative Staphylococcus (67%), methicillin-resistant coagulase-negative Staphylococcus (35%), with only 1 case of methicillin-sensitive Staphylococcus aureus (0.4%). Thirty-three patients (14%) developed an SSI. Of those with a positive Staphylococcus culture, only 54% received a concordant antimicrobial regimen, but this was not associated with an increased risk for infection ( P > 0.72). Conclusions: The use of perioperative antimicrobials whether concordant or discordant with the preoperative axillary microbial flora, specifically Staphylococci species, did not provide a significant impact on the risk of SSI.